2011
DOI: 10.1007/s00192-011-1468-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of l-arginine on bladder dysfunction following ovariectomy in a rabbit model

Abstract: Ovariectomy appreciably reduced bladder contractility. Treatment with L-arginine reversed the ovariectomy-induced bladder dysfunction. Decreased bladder contractile response was observed in the early days following ovariectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…We did not, however, observe any changes in the hypothalamic expression of Sh2b, Socs3, and Ptp1b by leucine deprivation (data not shown). Recent studies have demonstrated that Rho kinase (ROCK)1, in which the activity is influenced by nutritional status (51,52), increases phosphorylation of JAK2 and downstream activation of STAT3 to regulate leptin action (45). A possible role for ROCK1 in connecting leucine deprivation with the leptin pathway will be studied in the future.…”
Section: Discussionmentioning
confidence: 99%
“…We did not, however, observe any changes in the hypothalamic expression of Sh2b, Socs3, and Ptp1b by leucine deprivation (data not shown). Recent studies have demonstrated that Rho kinase (ROCK)1, in which the activity is influenced by nutritional status (51,52), increases phosphorylation of JAK2 and downstream activation of STAT3 to regulate leptin action (45). A possible role for ROCK1 in connecting leucine deprivation with the leptin pathway will be studied in the future.…”
Section: Discussionmentioning
confidence: 99%